2021
DOI: 10.3389/fimmu.2021.687961
|View full text |Cite
|
Sign up to set email alerts
|

γδ T Cells May Aggravate Acute Graft-Versus-Host Disease Through CXCR4 Signaling After Allogeneic Hematopoietic Transplantation

Abstract: Graft-versus-host disease (GVHD) is a pathology in which chemokines and their receptors play essential roles in directing the migration of alloreactive donor T cells into GVHD organs, thereby leading to further target tissue damage. Currently, acute GVHD (aGVHD) remains a major cause of high morbidity and mortality in patients who underwent allogeneic hematopoietic cell transplantation (alloHCT). The identification of immune cells that correlate with aGVHD is important and intriguing. To date, the involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…No commercial vaccine against CMV is available to date. Our previous study and preliminary data suggest that γδ T including Vδ1 + T‐cells do not induce allogeneic reactions [40]. The present study supports that Vδ1 + T‐cells have great potential for treating CMV infection.…”
Section: Discussionsupporting
confidence: 85%
“…No commercial vaccine against CMV is available to date. Our previous study and preliminary data suggest that γδ T including Vδ1 + T‐cells do not induce allogeneic reactions [40]. The present study supports that Vδ1 + T‐cells have great potential for treating CMV infection.…”
Section: Discussionsupporting
confidence: 85%
“…There was especially more IL-17A protein in the lesional mucosa of EOLP. Activated γδ T cells could amplify the Th17 response and induce αβ T cell immune responses, which aggravate graft-versus-host disease [ 40 ]. Psoriatic γδ T cells expressed IL-17A and activated keratinocytes in a IFN-γ and TNF-α-dependent manner [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other research has suggested that γδ T cells may have a negative impact in GvHD. Wu et al discovered that γδ T cells enhanced CD4 T-cell migration via the SDF-1–CXCR4 axis, exacerbating acute GvHD post allo HSCT [ 91 ]. As a result, more research into the influence and activities of γδ T cells in modulating GvHD is warranted.…”
Section: γδ T Cell Modulation Of Gvhdmentioning
confidence: 99%